Penerapan Metode Extream Programming Pada Sistem Informasi Manajemen di Lembaga Pembinaan Dewasa Al-Qur’an Sidoarjo - Syahri Mu’min; Awang Andhyka; Elmi Leonita Wahdin (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
WordPress is a content management system (CMS) that can be used to create websites. A content management system is an application that can help users create, manage, and edit websites more easily. By using a CMS, users do not need to master a programming language to be able to create a website. Lembaga Pembinaan Dewasa as non-formal educational institutions have many students who need to be processed to make it easier for leaders and administrators to determine policies. Processing student data via the web will be very easy and effective because it can be done anytime and effectively. The data here is student data from registration to learning groupings as well as teacher data. The process of making this application uses the Extream Programming method because this method is quite effective in developing small-scale applications. The stages in this method are Planning, Design, Coding and Testing. After the stages of making an application using this method, a web-based application is produced that can be used to manage student data at the Lembaga Pembinaan Dewasa Kecamatan Tulangan.